2001
DOI: 10.1021/jo0104936
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Partial Fluorination of Organic Compounds. 54.1 Anodic Mono- and Trifluorination of Thiochroman-4-one Derivatives and the Factors Affecting Product Selectivity

Abstract: Anodic fluorination of (E)-3-benzylidene-2,3-dihydrothiochroman-4-one and 3-benzyl-1-thiochromone derivatives under a variety of electrolytic conditions was found to provide selectively or exclusively the same fluorinated products: (E)-3-benzylidene-2,3-dihydro-2-fluorothiochroman-4-ones. In addition, di- and trifluorinated derivatives were also obtained depending on the starting heterocycles and electrolytic conditions. The factors affecting the product selectivity were also examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…306,307 These seminal studies constitute the first examples of selective electrochemical fluorination of chalcogen compounds. Since then, a variety of distinct sulfide-based motifs, such as 2H-benzo [b][1,4]-thiazin-3(4H)-one (114j), 308 benzothiazole (114o), 309-311 2,3-dihydrothiochroman-4-one (114k), 312 1,3-dithiolan-4-one (114c), 313 lactam (114a), 308 1,3,4-oxadiazole (114l), 311,314 1,3-oxathiolan-5-one (114b), 315 pyrimidin-4(3H)-one (114h), 316 phosphonate (114d), 317,318 pyridine (114e), 310,319 pyrimidine (114g), 310,311,319,320 quinazolin-4(3H)-one (114i), 319 quinoline (114f), 310 1,3,4-thiadiazole (114m), 311,314 and 1,2,4-triazole (114n), 314 have been shown to be amenable to regioselective monofluorination (Scheme 29). Because of their good conductivity, non-flammability, non-volatility and thermal stability, ionic liquids, such as Et 3 NÁnHF, have found widespread use as solvents in electrochemical fluorination reactions.…”
Section: Anodic Halogenationmentioning
confidence: 99%
“…306,307 These seminal studies constitute the first examples of selective electrochemical fluorination of chalcogen compounds. Since then, a variety of distinct sulfide-based motifs, such as 2H-benzo [b][1,4]-thiazin-3(4H)-one (114j), 308 benzothiazole (114o), 309-311 2,3-dihydrothiochroman-4-one (114k), 312 1,3-dithiolan-4-one (114c), 313 lactam (114a), 308 1,3,4-oxadiazole (114l), 311,314 1,3-oxathiolan-5-one (114b), 315 pyrimidin-4(3H)-one (114h), 316 phosphonate (114d), 317,318 pyridine (114e), 310,319 pyrimidine (114g), 310,311,319,320 quinazolin-4(3H)-one (114i), 319 quinoline (114f), 310 1,3,4-thiadiazole (114m), 311,314 and 1,2,4-triazole (114n), 314 have been shown to be amenable to regioselective monofluorination (Scheme 29). Because of their good conductivity, non-flammability, non-volatility and thermal stability, ionic liquids, such as Et 3 NÁnHF, have found widespread use as solvents in electrochemical fluorination reactions.…”
Section: Anodic Halogenationmentioning
confidence: 99%
“…Ethyl 2-benzyl-4,4-dimethyl-3-thiolanone-2-carboxylate (137) was reported to be electrolysed in Et 3 N·3HF/MeCN to give a mixture of trans/cis isomers of the highly biologically active 5-fluorothiolanone derivative 138 (Scheme 44). 90 Electrolytic fluorination of 2-(n-propyl)-1,3-dithiolan-4-one (139) was performed using Et 4 NF·4HF/MeCN to afford a cis/trans mixture of 5-fluoro-2-(n-propyl)-1,3-dithiolan-4-one (140) Recently, Dawood et al 93 the reported that electrolytic fluorination of the homoisothioflavone derivative 145 proceeds in a different manner to that of thioflavone (143), in Et 4 NF·4HF/DME affording mainly the 2-fluoro-3-benzylidenethiochromanone derivative 146 in addition to its di-and trifluorinated derivatives 147 and 148, respectively, as shown in Scheme 48. 93 The mono-and trifluorinated thiochromanone derivatives 146 and 148 were alternatively obtained from the direct electrolytic fluorination of 3-arylidenethiochroman-4-ones 149 under similar electrolytic conditions (Scheme 49).…”
Section: Aryl Sulfides the Fuchigamimentioning
confidence: 99%
“…93 The mono-and trifluorinated thiochromanone derivatives 146 and 148 were alternatively obtained from the direct electrolytic fluorination of 3-arylidenethiochroman-4-ones 149 under similar electrolytic conditions (Scheme 49). 93 2.1.14.3. Oxygen-containing heterocycles.…”
Section: Aryl Sulfides the Fuchigamimentioning
confidence: 99%
“…4 In addition, the anodic fluorination of (E)-3-benzylidenethiochroman-4ones was successfully carried out in Et 4 NF•4HF/DME to provide the corresponding monofluorinated products, fluorinated at the a-position to the sulfur atom. 5 Under the same electrolytic conditions, the anodic fluorination of (E)-3-benzylidenechroman-4-one derivatives was also achieved. 6 In contrast, the direct anodic fluorination of 3phenyl-2H-1,4-benzothiazine in triethylamine tris(hydrogen fluoride) (Et 3 N•3HF)/DME provided dimeric ben-zothiazine and its dehydro dimer in addition to the corresponding mono-, di-, and trifluorinated products in moderate total yield.…”
mentioning
confidence: 91%